Boardroom gender diversity and investment inefficiency: New evidence from the United Kingdom. (30th March 2022) - Farooq, Sanaullah; Gan, Christopher; Nadeem, Muhammad
Abstract: Research Question/Issue: Motivated by the recent regulatory reforms, in the forms of the UK Corporate Governance Code (UK CGC) in 2011 and the enaction of section 414C of the Companies Act 2006, to increase female representation on corporate boards, this study investigates the effect of boardroom gender diversity (BGD) on investment inefficiency (IE). These reforms were aimed at enhancing corporate governance by allowing a pool of female directors into directorship positions and bringing fresher and independent perspective of female directors, thus strengthening board monitoring and its internal control systems. This study therefore seeks to understand whether and how female directors align managers' and shareholders' interests by improving investment efficiency. Findings: Using a sample of UK listed firms from 2005 to 2018, this study provides the first empirical evidence on the impact of BGD on IE. Consistent with our theoretical predictions, we find a negative and statistically significant association between BGD and IE. Furthermore, in a difference‐in‐differences analysis, we find a significant impact of UK CGC on the BGD‐IE relationship. We also identify three possible channels (board dynamics, stewardship effect, and information environment) through which BGD is likely to affect IE. Finally, we also document that the said relationship is more pronounced in firms with three or more female directors, which is consistent with critical mass theory, and that BGD mitigates concerns surrounding both the underinvestment and overinvestment decisions. Our main results are robust to endogeneity bias, alternative measures of BGD and IE, and controlling for potential bias with a two‐step investment estimation method. Policy Implications: Our findings have important implications for regulators, policy‐makers, and other corporate stakeholders. Most importantly, the recent policy initiatives on improving representation of female directors can strengthen board monitoring and could reduce inefficient investments.